Tumor suppressor ARF: The new player of innate immunity - Través, Paqui G. (Landes Bioscience, 2012)
ARF (alternative reading frame) is one of the most important tumor regulator playing critical roles in controlling tumor initiation and progression. Recently, we have demonstrated a novel and unexpected role for ARF as modulator of inflammatory responses.